Popularizing Anti-Semitism in early modern Spain and its empire : Francisco de Torrejoncillo and the Centinela contra Judios (1674) - Soyer, Francois (Medieval and early modern Iberian world, 2014)
This book charts the history of the most vitriolic and successful anti-Semitic polemic printed in the early modern Hispanic world, offering the first analysis, edition and translation of the text: the Centinela contra judíos of the Franciscan Francisco de Torrejoncillo.